Implementasi Standar Koleksi Perpustakaan di Dinas Kearsipan dan Perpustakaan Kota Jambi berdasarkan Standar Nasional Perpustakaan (SNP 699: 2017) - Septiara, Dara; Miliani, Masyrisal; Yusufhin, Fridinanti (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2024)
Collection is the most important thing in the Library, but the collections contained must also comply with applicable standards. This study aims to evaluate the implementation of the National Library Standards (SNP 699: 2017) at the Archives and Library Service of Jambi City, especially related to the management of library collections. This study uses a descriptive qualitative approach with data collection methods, namely observation, interviews, and documentation. The method of determining the subjects in this study is by Purposive Sampling using the Miles and Huberman model analysis, namely data reduction, data display, and conclusion drawing/verification. The results of the study indicate that aspects that are in accordance with the SNP include types of collections, collections per capita, and collection preservation, which indicate the diversity of collections and attention to collection maintenance. Meanwhile, aspects of collection development and collection up-to-dateness are almost in accordance, although there are shortcomings in written policies and the number of recent collections that have not reached the standards required by the SNP. On the other hand, aspects that are not fully in accordance with the SNP include the procurement of library materials, where the budget allocated is much lower than the needs regulated by the SNP. Keywords: Collection management, National Library Standards, Public Library, SNP 699: 2017